2020
DOI: 10.1007/s12541-020-00434-5
|View full text |Cite
|
Sign up to set email alerts
|

Predict the Effects of Forming Tool Characteristics on Surface Roughness of Aluminum Foil Components Formed by SPIF Using ANN and SVR

Abstract: In the present work, multiple forming tests were conducted under different forming conditions by Single Point Incremental Forming (SPIF). In which surface roughness, arithmetical mean roughness (Ra) and the ten-point mean roughness (Rz) of AlMn1Mg1 sheet were experimentally measured. Also, an Artificial Neural Network (ANN) was used to predict the (Ra) and (Rz) by adopting the data collected from 108 components that were formed by SPIF. Forming tool characteristics played a key role in all the predictions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…Appropriate selection of the parameters of the sheet metal forming process using single point incremental forming (SPIF) is intended to ensure appropriate surface quality in terms of roughness and, at the same time, an economically justified forming time [ 1 , 2 ]. The basic parameters in the process are: tool rotational speed, feed rate, step size, size and shape of the tool, type of sheet metal, and tool path [ 3 , 4 , 5 ]. The lubricant also plays a very important role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate selection of the parameters of the sheet metal forming process using single point incremental forming (SPIF) is intended to ensure appropriate surface quality in terms of roughness and, at the same time, an economically justified forming time [ 1 , 2 ]. The basic parameters in the process are: tool rotational speed, feed rate, step size, size and shape of the tool, type of sheet metal, and tool path [ 3 , 4 , 5 ]. The lubricant also plays a very important role.…”
Section: Introductionmentioning
confidence: 99%
“…Alsaman et al [ 32 ] applied ANNs and the regression model to analyse the SPIF process for conical draw pieces. Najm and Paniti [ 4 ] used ANNs to predict the Ra and Rz parameters by adopting the data collected from frustum cones that were formed by SPIF. The results showed that an ANN with one argument in the output predicted the outcome sufficiently well when compared with a two-argument structure.…”
Section: Introductionmentioning
confidence: 99%
“…They found that predictive models of ANNs for Ra and Rz were characterised by performance measures of R 2 values between 0.657 and 0.979. In other studies, different tool materials and shapes were investigated experimentally to study factors including formability, geometric accuracy [ 31 ], and surface roughness [ 32 ] on an AlMn1Mg1 sheet formed using SPIF under various forming conditions. The researchers evaluated the performance of an Artificial Neural Network (ANN) and Support Vector Regression (SVR).…”
Section: Introductionmentioning
confidence: 99%
“…The SPIF process aims to form products with the most accurate shape possible [ 5 , 6 , 7 , 8 , 9 ]. A deep learning technique to propagate geometric accuracy in SPIF was proposed in [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [ 6 ], a Modified Adaptive Neuro-Fuzzy Inference System (MANFIS) focuses on geometric deviation prediction, and an Enhanced Squirrel Search Algorithm (ESSA) is used for the optimal selection of SPIF parameters in AA2024-O aluminum alloy sheets. Several shaping experiments have been carried out using SPIF under different forming conditions to measure the surface roughness, the arithmetic mean roughness (Ra), and ten-point mean roughness (Rz) of the AlMn1Mg1 sheet [ 7 ]. In addition, an ANN was used to predict (Ra) and (Rz), given the data collected from the SPIF components.…”
Section: Introductionmentioning
confidence: 99%